Ironless Lowfrequency Loudspeaker Working Under its Resonance Frequency - MERIT, Benoit; LEMARQUAND, Guy (Archives of Acoustics, 2008)
A soon achieved low frequency loudspeaker (10 Hz to 100 Hz) is described. To suppress the non-linearities and the drawbacks due to the motor, its structure is totally ironless. The large flat diaphragm and the high force factor of the loudspeaker lead to its high efficiency. Efforts have been made for reducing the non-linearities of the loudspeaker for a more accurate sound reproduction. Especially we have developed a motor totally made of permanent magnets, which create a uniform induction across the entire intended displacement of the coil. The motor linearity and the high force factor of the loudspeaker make it possible to work under its resonance frequency. This functioning needs the use of a DSP to raise the 12 dB/octave slope of the pressure response of the loudspeaker under its resonance frequency and to protect the moving pieces from large displacements. Results presented here are to be completed as soon as the loudspeaker will be achieved.